Cover Picture: Utility of the 2‐Nitrobenzenesulfonamide Group as a Chemical Linker for Enhanced Extracellular Stability and Cytosolic Cleavage in siRNA‐Conjugated Polymer Systems (ChemMedChem 1/2017). (5th January 2017) - Huang, Chih Hao; Takemoto, Hiroyasu; Nomoto, Takahiro; Tomoda, Keishiro; Matsui, Makoto; Nishiyama, Nobuhiro
Abstract : The front cover picture shows the excellent stability of the 2‐nitrobenzenesulfonamide linker outside the cell for use in constructing siRNA‐polymer conjugates for efficient siRNA delivery and release. The conjugates can be effectively and exclusively cleaved inside the cell due to the intracellular coexistence of reduced glutathione (GSH) and glutathione S‐transferase (GST). The linker can recognize the difference in redox potential across the cellular membrane with higher selectivity, compared with conventional disulfide linkers, and is also stable upon exposure to natural light. Thus, the 2‐nitrobenzenesulfonamide group can work as a new chemical linker with redox sensitivity for the molecular design of other biological stimuli‐responsive materials. More information can be found in the Communication by Hiroyasu Takemoto, Nobuhiro Nishiyama et al. onpage 19 in Issue 1, 2017 (DOI:10.1002/cmdc.201600488 ).